ENT 600 : Smart Vending Machine (Vmac-Tech) / Nor Fatin Hanani Mohd Besri ... [et al.] - Mohd Besri, Nor Fatin Hanani; Azmi Zulhasni, Nor Khairi Azmi; Mohd Amin, Atiqa Aisya Niesya; Rosman, Muhammad Zulhilmi (2019)
Smart Vending Machine will provide a' unique features that helps vending machine operator and the community located in certain areas such as bus station, railway station, and colleges in Malaysia. Our product is emphasized on the unique features which are application to monitor the stock of product and the cashless payment method. Indirectly, this encourage people to purchase at vending machine with saving time as it is the convenience.